Examining Privilege in Engineering Socialization Through the Stories of Newcomer Engineers. Issue 2 (4th May 2021) - Beddoes, Kacey
ABSTRACT: Prior research has demonstrated that early career socialization experiences play an important role in career outcomes, including learning, performance, satisfaction, and retention. What is not yet well understood, however, is how the organizational socialization experiences of different groups of early career engineers vary and how such variation leads to different career outcomes. By examining the experiences of first year engineers, this article contributes new insights into factors affecting socialization experiences and draws attention to privilege as an important factor shaping engineering socialization experiences. The stories of negative interpersonal interactions experienced by first year women civil engineers are presented and used to glean forms of privilege that affect newcomer socialization. The primary forms of intersectional privilege identified stem from gender and race, with religion and nationality also shaping newcomer experiences. The stories are used to inform proposed additions to a model of engineering socialization.